2001
DOI: 10.1067/mtc.2001.115423
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenic proteins in the lungs of children after cavopulmonary anastomosis

Abstract: Lung biopsy specimens from children after cavopulmonary anastomosis demonstrate increased expression of vascular endothelial growth factor and its receptor. These data confirm earlier findings that blood vessels forming after cavopulmonary anastomosis may have reduced intercellular junctions (decreased CD31 staining). Despite the increased numbers of pulmonary vessels that are present in these patients, these vessels are not highly proliferative (proliferating cell nuclear antigen staining equivalent to that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 0 publications
3
29
0
Order By: Relevance
“…After cavopulmonary anastomosis, pulmonary microvessel density is increased even in the absence of clinically apparent pulmonary arteriovenous malformations, supporting the presence of constant angiogenic stimuli (40). Lung biopsy specimens from children after cavopulmonary anastomosis had increased expression of VEGF and its receptor (41).The mechanism whereby the pulmonary circulation processes IL-8 and the potential role of IL-8 in the pathogenesis of angiogenesis warrant further study.…”
Section: Accepted Manuscriptmentioning
confidence: 92%
“…After cavopulmonary anastomosis, pulmonary microvessel density is increased even in the absence of clinically apparent pulmonary arteriovenous malformations, supporting the presence of constant angiogenic stimuli (40). Lung biopsy specimens from children after cavopulmonary anastomosis had increased expression of VEGF and its receptor (41).The mechanism whereby the pulmonary circulation processes IL-8 and the potential role of IL-8 in the pathogenesis of angiogenesis warrant further study.…”
Section: Accepted Manuscriptmentioning
confidence: 92%
“…Clinically heparin has been used in the patients associated with congenital heart disorders because development of pulmonary vascular bed is mandatory prior to open-heart surgery in order to achieve successful clinical outcome (Geggal et al 1990;Starnes et al 2000Starnes et al , 2001. Heparin administration to these patients above induce vascular proliferation, which could contribute to cordial operation.…”
Section: Discussionmentioning
confidence: 99%
“…Heparin administration to these patients above induce vascular proliferation, which could contribute to cordial operation. Heparin is also considered to be involved in the regulation of neonatal pulmonary artery development chiefly through its ability to promote angiogenesis in conjunction with various growth factors (Leopald et al 1998;Starnes et al 2001). However it is also true that its angiogenesis-promoting effects were not necessarily well characterized.…”
Section: Discussionmentioning
confidence: 99%
“…[20] For example, in a clinical study, Jabbour and colleagues reported that a higher proliferation rate in endothelial cells isolated from cerebral arteriovenous malformations was associated with increased levels of vascular endothelial growth factor (VEGF)-A and VEGF receptors [21]. Recent findings from clinical and experimental studies have implicated similar pro-angiogenic processes to be operative in PAVM development in the post-SCPC setting [22].…”
Section: Introductionmentioning
confidence: 99%
“…[37] While angiogenic pathways have been recognized in many normal and pathologic physiologic processes including arterio-venous malformations,[20,21,31] there are currently no established molecular mechanisms that have been linked to PAVM formation. The lack of understanding of molecular mechanisms may explain the absence of non-surgical, non-invasive, treatment(s) for PAVMs.…”
Section: Introductionmentioning
confidence: 99%